Changes on degree of conversion of dual-cure luting light-cured with blue LED - Bandéca, M. C.; El-Mowafy, O.; Saade, E. G.; Rastelli, Alessandra Nara de Souza [UNESP]; Bagnato, V. S.; Porto-Neto, S. T. (Pleiades Publishing, 2009)
The indirect adhesive procedures constitute recently a substantial portion of contemporary esthetic restorative treatments. The resin cements have been used to bond tooth substrate and restorative materials. Due to recently introduction of the self-bonding resin luting cement based on a new monomer, filler and initiation technology has become important to study the degree of conversion of these new materials. In the present work the polymerization reaction and the filler content of dual-cured dental resin cements were studied by means of infra-red spectroscopy (FT-IR) and thermogravimetry (TG). Twenty specimens were made in a metallic mold (8 mm diameter × 1 mm thick) from each of 2 cements, Panavia® F2.0 (Kuraray) and RelyX™ Unicem Applicap (3M/ESPE). Each specimen was cured with blue LED with power density of 500 mW/cm 2 for 30 s. Immediately after curing, 24 and 48 h, and 7 days DC was determined. For each time interval 5 specimens were pulverized, pressed with KBr and analyzed with FT-IR. The TG measurements were performed in Netzsch TG 209 under oxygen atmosphere and heating rate of 10°C/min from 25 to 700°C. A two-way ANOVA showed DC (%) mean values statistically significance differences between two cements (p < 0.05). The Tukey's test showed no significant difference only for the 24 and 48 h after light irradiation for both resin cements (p > 0.05). The Relx-Y™ Unicem mean values were significantly higher than Panavia® F 2.0. The degree of conversion means values increasing with the storage time and the filler content showed similar for both resin cements. © 2009 Pleiades Publishing, Ltd.
Keywords: Blue LEDs; Degree of conversion; Dental resins; Dual-cure; Filler contents; Kuraray; Light irradiations; Luting cements; Mean values; Metallic mold; New material; Oxygen atmosphere; Polymerization reaction; Power densities; Resin cement; Restorative materials; Storage time; Thermogravimetry; Time interval; Two-way ANOVA; Curing; Dental cement; Fillers; Oxygen; Resins; Cements